Speech Melody and the Evolution of the Minimalist Aesthetic in Steve Reich’s The Cave - Prieto, Eric (Circuit, 2002)
This paper seeks to explain Reich's use of the "speech melody" technique in his video opera The Cave in terms of the minimalist reliance on impersonal processes and the economical use of musical material. For this piece Reich uses digitally sampled speech fragments with an emphatic melodic contour as the basis for composition. These speech melodies provide the primary building blocks out of which the work is constructed. Because the musical material is actually contained in the verbal material, Reich is able to provide innovative solutions to some of the traditional problems facing the composer of vocal music. This technique not only enables Reich to reintroduce a compelling expressive element into his work, but also enables him to reconcile the composer's search for rigorously autonomous musical structures with his documentary interest in the subjective concerns and social problems of the outside world.